Abordagem do território na constituição da integralidade em saúde ambiental do trabalhador na atenção primária em Quixeré-CE - Pessoa, Vanira Matos (2010)
Addresses the health practices in the SUS, with the object of analysis the development of actions in environmental health and worker at primary health care (PHC) in Quixeré-Ceará. Was taken as the base area and undertook a perspective on the transformation processes under the economic development model promoter of changes in the way of life of communities and workers. The objective was to contribute to the effectiveness of policy and environmental health worker in PHC, realizing the territorial (social map, labor and environmental) that have a dialogue with the health needs and quality of life in the territory. We used action research, forming a group of 14 persons representing the City Council Health, social movements, agricultural workers, users of SUS association, PHC professionals, teachers and councilors to discuss the intersection of these fields in the APS and propose actions in the Family Health Strategy (FHS) and the city. This research resulted in the redefinition and recognition of the territory, arising from the interpretation of the subject and approach to the issues of community interest. The appropriation of the territory took place as the group rethought the model of economic development, highlighting problems such as land tenure, ie, loss of land by peasants, promoting the expulsion from the countryside to the urban periphery, constituting labor employed with an intense flow of people, contributing to the worsening of social problems like prostitution, drug addiction and violence. It was identified that the agro-export model of agriculture implies deforestation, exhaustive use of land, water and agrochemicals, leading to the extinction of animals and plants associated with the generation of unproductive soil, typical impacts to human health as changes in eating habits, work and culture, favoring the increase of obesity, hypertension, psychological problems, malnutrition, allergies and persistence of diseases such as Chagas worms, dysentery, dengue fever, among others. Stood out as potential agribusiness generates harm the health of workers and communities, overwhelming public policies, especially health services that are new in coping with work-environment issues. APS refers difficulties in operationalizing the health worker provided guaranteed access to comprehensive health care, prioritizing care actions for specific groups. Associated to this the weakness of the government in the supervision and support to communities before the agricultural modernization conservative who seizes and uses indiscriminately the territory. The group proposed an action plan which highlights the need for joint action of public policies (disciplinary and intersectoral) in addressing the problems related to work-environment, including the local and global impacts are unevenly felt and lived by different social sectors, promoting a fertile ground for rethinking and restructuring the responsibilities of municipal management. Points to the involvement of the population as a path to social transformation of local base, expanding the exercise of power by social control and social movements, understanding the complexity of reality, locking EU debates, political and ideological reflecting and expressing the aspirations of the people the plateau of Apodi-CE.